Anti-angiogenic effect of Artocarpus heterophyllus seed methanolic extract in ex ovo chicken chorioallantoic membrane - Swastika Oktavia; Nastiti Wijayanti; Bambang Retnoaji (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To examine the anti-angiogenic potential of Artocarpus heterophyllus (A. heterophyllus) seed extract in chicken chorioallantoic membrane (CAM). Methods: This study used chicken CAM ex ovo culture to examine the potential anti-angiogenic activity of A. heterophyllus seed methanolic extract. Basic fibroblast growth factor was used to induce the ectopic formation of blood vessels on CAM treated with extract. Blood vessel number was assessed by macroscopic and microscopic observation, and compared and analyzed for all treatments and controls. Results: Macroscopic observation revealed that a dose of 35 μg/mL of methanolic extract of A. heterophyllus seeds could inhibit basic fibroblast growth factor-induced angiogenesis by 61% in chicken CAM ex ovo culture. This concurred with microscopic observations on the histological structure of blood vessels, which indicated that extract treatment repressed the formation of new blood vessels. Conclusions: This is the first study to report the anti-angiogenic effect of methanolic extract derived from A. heterophyllus seeds and its potential as a candidate for future anticancer therapy.